FACTORS OF INTEREST AND MOTIVATION IN THE ORGANIZATION OF INDEPENDENT WORK OF STUDENTS - Eshmurodov Azamat G‘uzorovich (American Journals, 2025)
The article is devoted to the factors and directions of increasing and strengthening interest and motivation in science for organizing independent education of students of technical specialties. In the state, one of the biggest pressing problems is the interest of students in independent learning in science lessons. Motivation is a way to increase a student’s interest in science; it is a type of independent activity that has occupied an important place for the student in education. The article analyzes motivational values and concepts that are recognized by many students as an important factor in students' independent learning. Motivation in organizing self-study in the field of information technology for technical education students is one of the pressing issues of our time. In the credit system, the volume of training for auditors is 40%, and the volume of training for self-study is 60%. According to this development of motivation, the development of educational knowledge during independent learning by students is today considered a complex interdisciplinary problem.
Keywords: Motivation, factor, need, activity, driving factor, motive, Maslow's pyramid.